RISKS AFFECTING THE FINANCIAL STABILITY OF INSURANCE COMPANIES AND THEIR ASSESSMENT METHODS (Marketing Journal, 2025)
This article discusses the factors affecting the financial stability of insurance companies, the risks that arise, methods for assessing them, indicators for assessing the financial stability of insurance companies, and methods for mathematically analyzing insurance risk and the financial stability of insurance companies.
Keywords: insurance companies; financial stability; risks; risk assessment methods; mathematical modeling; insurance policy; insurance claims